Capitalism, socialism, and the politics of difference in the Colombia-Venezuela borderland - Price, D (2025)
This thesis examines the politics and production of social difference in the Colombia- Venezuela borderland, focusing on how political-economic ideologies—capitalism and socialism—serve as primary axes of differentiation in host-migrant relations. Through 17 months of ethnographic fieldwork in La Guajira, Colombia, I analyze how capitalism and socialism are discursively constructed as emic categories and how these labels ‘stick’ to the bodies of Venezuelan migrants, framing them as undesirable ‘socialist’ subjects. Building on anthropological works about the ‘state effect,’ here I propose the concept of an ‘ideological effect’ that is central to this analysis, illustrating how the capitalist-socialist binary is maintained to ostracize socialism and sustain neoliberal capitalism as the dominant norm. Throughout its chapters, I explore how the emergence of this symbolic geography between capitalism and socialism shapes local dynamics and marks Venezuelan migrants as ‘socialist’ subjects, embedding the labels in everyday interactions. I explore the historical and ongoing impacts of neoliberal policies in La Guajira, revealing how these have deepened economic precarity among my Colombian interlocutors, who often direct their frustrations toward Venezuelan migrants rather than toward the structural economic forces at play—demonstrating the powerful role the ‘ideological effect’ has in shaping and directing local discourse. Additionally, I examine how ideological markers become embedded in everyday practices and discourses, from narratives about ‘hard work’ and ‘laziness’ to the differential access to public utilities like electricity, all of which contribute to the construction of difference in the borderland. By analyzing key symbols such as labor practices, social services, and local discourses surrounding migration, I show how the boundaries between capitalism and socialism are over- emphasized and maintained through ideological work. I demonstrate that these categories are not fixed or naturally occurring, but rather require constant reproduction to sustain the broader political economy of neoliberal capitalism. In doing so, I challenge the binary distinctions between these systems, revealing hybrid forms of governance and economic life that blur the lines between capitalism and socialism. Overall, I contribute to debates on the anthropology of difference by focusing on political-economic ideologies as key markers of social distinction, expanding beyond traditional categories like race, ethnicity, religion, or nationality in host-migrant contexts. I also interrogate the construction of capitalism and socialism as discrete, bounded systems, arguing instead that they are discursive categories that require active maintenance. Lastly, I show how global political economy is experienced by everyday people at the Colombia-Venezuela border, revealing how broader economic forces shape local perceptions, tensions, and exclusions.